Eight Noble Opinions and the Economic Crisis: Four Literary-philosophical Sketches à la Eduardo Galeano - Giorgio Baruchello (The University of Akureyri, 2010)
Four literary-philosophical skecthes are presented here in order to celebrate the ten-year anniversary of the publication of the official English translation of one of Eduardo Galeano's most important books: Upside Down: A Primer for the Looking-glass World. Each of these four sketches deals with the current economic crisis, though from different perspectives of analysis, and attempts to make use of the vibrant and creative sylistic devices characterising Galeano's works, particularly Upside Down. In this book, Galeano explored insightfully the roots of the crisis to come. His critical conclusions were analogous to those of another eccentric observer of the most notable economic phenomena of the 1990s, John McMurtry, whose perception of the looming crisis was even more profound and technical. Therefore, also this Canadian thinker, indeed his theory of value, is evoked in the four sketches, for McMurtry's onto-axiology reveals the ongoing contradiction between the relentless search for profit of the mostly virtual global script type=text/javascript src=http://nome.st5.stefna.is/joomla/plugins/editors/jce/tiny_mce/themes/advanced/langs/en.js?version=156/scriptscript type=text/javascript src=http://nome.st5.stefna.is/joomla/plugins/editors/jce/tiny_mce/plugins/advcode/langs/en.js?version=156/scripteconomy and the requirements of natural and human life.